Parametric design-based modal damped vibrational piezoelectric energy harvesters with arbitrary proof mass offset: Numerical and analytical validations. (February 2016) - Lumentut, Mikail F.; Howard, Ian M.
Abstract: This paper focuses on the primary development of novel numerical and analytical techniques of the modal damped vibration energy harvesters with arbitrary proof mass offset. The key equations of electromechanical finite element discretisation using the extended Lagrangian principle are revealed and simplified to give matrix and scalar forms of the coupled system equations, indicating the most relevant numerical technique for the power harvester research. To evaluate the performance of the numerical study, the analytical closed-form boundary value equations have been developed using the extended Hamiltonian principle. The results from the electromechanical frequency response functions (EFRFs) derived from two theoretical studies show excellent agreement with experimental studies. The benefit of the numerical technique is in providing effective and quick predictions for analysing parametric designs and physical properties of piezoelectric materials. Although analytical technique provides a challenging process for analysing the complex smart structure, it shows complementary study for validating the numerical technique. Highlights: New electromechanical finite element-based modal damped vibration model is developed. New closed-form boundary value technique-based modal damped vibration model is developed. Two theoretical models are compared for modelling piezoelectric energy harvester. The effect of parametric identification and optimisation studies is included. Optimal power harvesting frequency responses and the corresponding frequency bandwidth.